2019
DOI: 10.1080/14681994.2019.1574970
|View full text |Cite
|
Sign up to set email alerts
|

Culturally competent health care for sex workers: an examination of myths that stigmatize sex work and hinder access to care

Abstract: Sex workers are individuals who offer sexual services in exchange for compensation (i.e., money, goods, or other services). Within the United States the full-service sex work (FSSW) industry generates 14 billion dollars annually there are estimated to be 1-2 million FSSWers, though experts believe this number to be an underestimate. Many FSSWers face the possibility of violence, legal involvement, and social stigmatization. As a result, this population experiences increased risk for mental health disorders. Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 48 publications
1
50
0
4
Order By: Relevance
“…To overcome this problem, we recommend the use of a nine-valent vaccine (9vHPV) instead of the bivalent and quadrivalent vaccines. The 9vHPV vaccine contains type 6,11,16,18,31,33,45,52, and 58 which was approved by the FDA in December 2014, and by the European Medicines Agency (EMA) in June 2015 [100].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, we recommend the use of a nine-valent vaccine (9vHPV) instead of the bivalent and quadrivalent vaccines. The 9vHPV vaccine contains type 6,11,16,18,31,33,45,52, and 58 which was approved by the FDA in December 2014, and by the European Medicines Agency (EMA) in June 2015 [100].…”
Section: Discussionmentioning
confidence: 99%
“…18,31,33,35,39,45,51,52,56,58,59, 66, 68, 73 and 82 are considered high risk genotypes, whereas low-risk genotypes include HPV- 6,11,34,40,42,43,44,54,61,70,72,81, and 89 [4]. There are three available HPV vaccines licensed by the U.S. Food and Drug Administration (FDA): quadrivalent HPV vaccine, including HPV types 6,11,16 and 18 (Gardasil®, produced by Merck); bivalent HPV vaccine, including HPV types 16 and 18 (Cervarix™, produced by GlaxoSmithKline), and nine-valent vaccine, including HPV types 6,11,16,18,31,33,45,52 and 58 (Gardasil 9; produced by Merck) [5,6]. Previous reports suggested that 65%-100% of the sexually active population are exposed to HPV during their lifespan [7].…”
Section: Introductionmentioning
confidence: 99%
“…18,31,33,35,39,45,51,52,56,58,59,66,68,73 and 82 are considered high risk genotypes, whereas low-risk genotypes include HPV- 6,11,34,40,42,43,44,54,61,70,72,81, and 89 [4]. There are three available HPV vaccines licensed by the U.S. Food and Drug Administration (FDA): quadrivalent HPV vaccine, including HPV types 6, 11, 16, and 18 (Gardasil®, produced by Merck); bivalent HPV vaccine, including HPV types 16 and 18 (Cervarix™, produced by GlaxoSmithKline), and nine-valent vaccine, including HPV types 6,11,16,18,31,33,45,52 and 58 (Gardasil 9; produced by Merck) [5,6]. Previous reports suggested that 65%-100% of the sexually active population are exposed to HPV during their lifespan [7].…”
Section: Introductionmentioning
confidence: 99%
“…CE is also critical for the development of adapted and sustainable prevention programmes among sex workers . Finally, it is necessary to address stigma related to sexual preferences, drug use, sex work and PrEP use .…”
mentioning
confidence: 99%